(untitled) (Research, Society and Development, 2025)
The determination of soil shear strength constitutes one of the main challenges in geotechnical engineering, as it is a fundamental parameter for the design of safer and economically viable projects. In slope stability analyses, particularly those involving long-term displacements, the quantification of residual shear strength is crucial; this strength is typically determined through laboratory testing. Therefore, the present study aimed to conduct a literature review on the testing methods employed for obtaining the residual strength of soils. The investigation included the application of multiple reversal direct shear tests, polished interface direct shear tests, and torsional shear tests (ring shear) to assess the residual strength of a calcareous clay from a slope located in the municipality of Paulista, State of Pernambuco (PE). It was found that only the polished interface direct shear test resulted in divergent values compared to the other methods and the data reported in the specialized literature. In the multiple reversal test, the residual friction angle reached approximately 26°, while the ring shear test recorded 24,6º. These high friction angle values are intrinsically associated with the soil’s mineralogical composition.